2018
DOI: 10.1002/ecy.2222
|View full text |Cite
|
Sign up to set email alerts
|

Negligible effect of competition on coral colony growth

Abstract: Competition is an important determinant of assemblage structure and population regulation, often resulting in decreased growth, fecundity or survival. In corals, most studies testing for an effect of competition on demographic traits, such as growth, have been experimental and often impose very high levels of competition upon colonies. To more realistically assess the role of competition on coral traits, multispecies studies in the wild are required. Here, we use 5 yr of data that includes 11 coral species on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 57 publications
(90 reference statements)
0
18
0
Order By: Relevance
“…) or changes in competitive interactions (Álvarez‐Noriega et al. ), suitable data are rarely available. Ultimately the abundance of colonies over depth does not necessarily indicate a refuge for the population, which must produce larvae capable of reaching and successfully colonizing shallow habitats.…”
Section: Resultsmentioning
confidence: 99%
“…) or changes in competitive interactions (Álvarez‐Noriega et al. ), suitable data are rarely available. Ultimately the abundance of colonies over depth does not necessarily indicate a refuge for the population, which must produce larvae capable of reaching and successfully colonizing shallow habitats.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, we found that light explains only 10% of the variation, suggesting that biotic factors might have a greater contribution. For example, a lack of suitable competitors that can also withstand the unique mesophotic conditions, particularly during their earlylife stages (Álvarez-Noriega et al, 2018), allows corals to grow without suppression from such neighboring competitors. Additionally, demographic traits (such as growth rate) that are linked to a species' life-history strategies may affect its size-distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Since all aquariums were filled with seawater from the same pipe and some healthy giant clams in T assemblages harbored the Vibrionaceae species at a lower proportion, the prevalent hypothesis is an increased susceptibility of infection due to the presence of corals. Benthic species, particularly corals, are highly competitive [60] and have been classified based on their aggressiveness [61][62][63][64]. Corals compete either by direct physical contact or via the production and secretion of secondary metabolites that can weaken or kill neighboring organisms [65][66][67][68][69][70].…”
Section: The Composition Of Benthic Species Assemblages Influences Thmentioning
confidence: 99%